2017
DOI: 10.1515/ceer-2017-0053
|View full text |Cite
|
Sign up to set email alerts
|

Spergilli on Building Partitions Infested with Moulds in Residential Housing and Public Utility Premises

Abstract: A b s t r a c tAspergilli constitute a serious risk to the health of the inhabitants of infested rooms. Mycological analysis conducted in buildings infected with moulds in the area of the Lubuskie province (Poland) demonstrated the presence of 9 species of Aspergillus moulds: A. carbonarius A. clavatus, A. flavus, A. fumigatus, A. niger, A. ochraceus, A. terreus, A ustus and A. versicolor. The highest frequency (4 -frequently) was observed in the case of A. versicolor, while frequency 3 (fairly frequently) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…According to IARC, STEG is classified in group 2B "Possibly carcinogenic to humans" [52] because it can induce tumors including hepatocellular carcinomas, liver haemangiosarcomas, angiosarcomas in brown fat, and lung adenomas in several species [87]. However, in comparison with AFB 1 , STEG toxicity has been assessed to be 10 or even up to 100 times lower [88,89]. Due to the minor significance of STEG in this review, its chemical structure is not shown in Table 2.…”
Section: Sterigmatocystinmentioning
confidence: 99%
“…According to IARC, STEG is classified in group 2B "Possibly carcinogenic to humans" [52] because it can induce tumors including hepatocellular carcinomas, liver haemangiosarcomas, angiosarcomas in brown fat, and lung adenomas in several species [87]. However, in comparison with AFB 1 , STEG toxicity has been assessed to be 10 or even up to 100 times lower [88,89]. Due to the minor significance of STEG in this review, its chemical structure is not shown in Table 2.…”
Section: Sterigmatocystinmentioning
confidence: 99%
“…Environmental pollution by heavy metals, i.e., Pb, Cu, Fe, R, Ni, Zn, Cr, Cd, Mo and metalloids (Se, As) is a serious global problem resulting from the intensive progress of civilization [1][2][3]. One of the most dangerous elements on Earth is mercury, since it occurs in liquid, gas or a solid form and is an element of a high volatility, easily spreading in the atmosphere [4].…”
Section: Introductionmentioning
confidence: 99%